If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 9 + -2(x + 5) = 4x + -2(3 + -1x) Reorder the terms: 3x + 9 + -2(5 + x) = 4x + -2(3 + -1x) 3x + 9 + (5 * -2 + x * -2) = 4x + -2(3 + -1x) 3x + 9 + (-10 + -2x) = 4x + -2(3 + -1x) Reorder the terms: 9 + -10 + 3x + -2x = 4x + -2(3 + -1x) Combine like terms: 9 + -10 = -1 -1 + 3x + -2x = 4x + -2(3 + -1x) Combine like terms: 3x + -2x = 1x -1 + 1x = 4x + -2(3 + -1x) -1 + 1x = 4x + (3 * -2 + -1x * -2) -1 + 1x = 4x + (-6 + 2x) Reorder the terms: -1 + 1x = -6 + 4x + 2x Combine like terms: 4x + 2x = 6x -1 + 1x = -6 + 6x Solving -1 + 1x = -6 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. -1 + 1x + -6x = -6 + 6x + -6x Combine like terms: 1x + -6x = -5x -1 + -5x = -6 + 6x + -6x Combine like terms: 6x + -6x = 0 -1 + -5x = -6 + 0 -1 + -5x = -6 Add '1' to each side of the equation. -1 + 1 + -5x = -6 + 1 Combine like terms: -1 + 1 = 0 0 + -5x = -6 + 1 -5x = -6 + 1 Combine like terms: -6 + 1 = -5 -5x = -5 Divide each side by '-5'. x = 1 Simplifying x = 1
| (y-9)(y-6)=0 | | 10y-3=-8-4y | | 2x^2=1-5 | | Y=-5+-3X | | (m+1)x=a-1 | | 2(3X+4)-2X=7X-3(-2X+11) | | -6(-1-3x)=96 | | 5/5/6-3/1/3 | | T(n)=100n+5 | | 87(-5)+9(9(-5)-4)= | | -2(8+6x)=-40 | | x^2+38x+3=0 | | (x-3)2+(y-5)2=81 | | 54/9=n/7 | | 21=d | | -105+4(-2(2)+3(-5))+8(2)= | | 3000=2X*X/2 | | -4(6x+2)=280 | | Ln(x-3)=o | | -5-3(8n+6)=-113 | | 23(-5)+10= | | 7x-1237=4x+20816 | | 2(-6+x)=-14 | | -3x-10=x+26 | | -13+2x=-52-17x | | -4(-5+7x)=-176 | | (6X-5)+(7X+8)=90 | | 90x^2-45xy+63x=0 | | 2+4x=7x-19 | | 4x(2x-6)=0 | | -4(-2x+7)=-12 | | 4(1+5r)=23+r |